Use of Antidepressant for the Treatment of Depression in CAMHS Outpatient - Chidimma Orji; Linda Robinson (BJPsych Open)
Aims: According to NICE guidelines children and young people with depression should be treated on an outpatient basis. Antidepressants should not be offered routinely to a child or young person with moderate to severe depression except in combination with a concurrent psychological therapy.